AKT inhibitor MK-2206 sensitizes breast cancer cells to MLN4924, a first-in-class NEDD8-activating enzyme (NAE) inhibitor. Issue 16 (18th August 2018) - Chen, Xiaoyu; Cui, Danrui; Bi, Yanli; Shu, Jianfeng; Xiong, Xiufang; Zhao, Yongchao
ABSTRACT: Breast cancer is a common type of cancer among female cancer patients and the main cause of cancer-related deaths. During the last decades, targeted therapies for breast cancer have been rapidly developing. Among them, MLN4924, a first-in-class NEDD8-activating enzyme (NAE) inhibitor, has performed antitumor activity by inactivating the cullin-RING ligases and causing the accumulation of their substrates to induce apoptosis in a number of studies. In this study, we found that MLN4924 activates the AKT pathway in both HER2-positive and triple-negative breast cancer (TNBC) cell lines. Given that AKT signaling is responsible for tumor progression and drug resistance in some types of cancers, we hypothesized that the AKT inhibitor may synergistically enhance the tumor suppression capability in breast cancer by MLN4924. To demonstrate the sensitizing effect, MK-2206 was chosen as the adjuvant treatment, and cell growth, migration and apoptosis were detected. The results showed that MLN4924 treatment inhibited cell growth and migration and induced apoptosis in both SK-BR3 and MDA-MB231 breast cancer cell lines. More importantly, the combined treatment of MLN4924 and MK-2206 indeed caused stronger cytotoxicity and inhibition of migration and a much higher induction of apoptosis compared with MLN4924 treatment alone. Our study provides the proof-of-concept evidence for strategic drug combination of MLN4924 with an AKT inhibitor for maximal killing of breast cancer cells via the enhancement of apoptosis.